Patogenost izolatov izbranih vrst gliv na Pinus sylvestris L. IN P. nigra Arnold - Ana Brglez; Barbara Piškur; Nikica Ogris (Acta Silvae et Ligni, 2023)
The pathogenicity of eight selected fungal isolates (Corinectria fuckeliana, Diaporthe eres, Diplodia pinea, Fusarium sp. 1 and 2, Fusicolla sp., Nectria dematiosa and Tympanis sp.), isolated from diseased pines in Slovenia in 2020 and 2021, was tested on seedlings of Scots and Austrian pine. We inoculated a total of 115 pine seedlings (including the control group), regularly checked their health status and performed re-isolations from necrotic margins at the first signs of desiccation. Re-isolations were successful only when inoculated with Diplodia pinea, Diaporthe eres and Fusarium sp. 2. The average length of necrosis in Scots pine seedlings inoculated with D. pinea, Di. eres and Tympanis sp. was significantly different from that of the control group (p < 0.05). In Austrian pine seedlings, the average length of necrosis differed significantly between the control group and seedlings inoculated with the fungi D. pinea and Tympanis sp. (p < 0.05).